Implementasi Manajemen Strategik Dalam Meningkatkan Mutu Pendidikan Madrasah Ibtidaiyah Darunnajah - Muh Habibulloh Habib; Imam Fuadi; Prim Masrokan Mutohar (eL Bidayah: Journal of Islamic Elementary Education, 2023)
Quality of Education will succeed with the right strategic management. So far, management implementation has had several problems, including teacher professionalism, graduate competency standards, effective learning and programs without consideration. In order to get a complete picture, the researcher uses a type of qualitative descriptive research conducted at Islamic Elementary Darunnajah Trenggalek. The results of the study show that Islamic Elementary Darunnajah describes the vision, mission, goals, objectives and profile of madrasah resources. strategy implementation at Islamic Elementary Darunnajah is carried out through internal and external madrasa environmental activities which are described through the madrasah organizational structure, person in charge of activities, job descriptions, study days and times, financing budget, curriculum, school promotion, new student admissions, school culture, code of ethics schools, school policies, geographic, demographic, cultural and community appreciation, involvement of school committees, developments in science and technology, partner institutions and strategic implementation in meeting national education standards (MI). This step creates new awareness in schools about the importance of using quality standards in carrying out activities or programs. [Mutu Pendidikan akan berhasil dengan adanya manajemen strategi yang tepat. Selama ini, implementasi manajemen mempunyai beberapa permasalahan, diantaranya profesionalisme guru, standar kompetensi lulusan, pembelajaran efektif dan program-program tanpa pertim-bangan. Guna mendapatkan gambaran yang utuh, maka peneliti menggunakan jenis penelitian deskriptif kualitatif yang dilakukan pada Madrasah Ibtidaiyah Darunnajah Trenggalek. Hasil penelitian bahwa Madrasah Ibtidaiyah Darunnajah mendeskripsikan visi, misi, tujuan, sasaran dan profil sumber daya madrasah. implementasi strategi pada Madrasah Ibtidaiyah Darunnajah dilakukan melalui aktivitas lingkungan internal dan eksternal madrasah yang dideskripsikan melalui struktur organisasi madrasah, penanggung jawab kegiatan, job deskripsi, hari dan waktu belajar, anggaran pembiayaan, kurikulum, promosi sekolah, penerimaan siswa baru, budaya sekolah, kode etik sekolah, kebijakan sekolah, keberadaan lingkungan geografis, demografis, lingkungan budaya dan apresiasi masyarakat, keterlibatan komite sekolah, per-kembangan ilmu pengetahuan dan teknologi, lembaga Mitra dan implementasi strategik dalam memenuhi standar (MI) pendidikan nasional. Langkah ini menjadikan kesadaran baru di sekolah tentang pentingnya menggunakan standar mutu dalam melakukan kegiatan atau program-program]